Daily activities of working individuals with hearing and speech disabilities (Journal of Health Sciences, 2017)
IntroductionDisability is one of the factors that can lead to social exclusion and poverty of individuals with hearing and speech impairment. This is due to the fact that individuals with disabilities are often underestimated, in terms of their work and social skills. The employment of people with disabilities represents a powerful mechanism for achieving full participation of the marginalized groups in all spheres of society.MethodsThe study included a total of 40 people with hearing and speech disabilities, out of which 16 individuals were employed at DES d.o.o. Sarajevo and 24 at SINKRO d.o.o. Sarajevo. A combination of three questionnaires was used for assessing daily activities and their impact on the quality of life (QoL) of the individuals with hearing and speech disabilities.ResultsIn the total sample, there were 35% males and 65% females. Complete deafness was observed in the majority of participants (90%), while the rest had either moderate (7.5%) or mild (2.5%) hearing impairment. A higher number of participants used sign language as the means of communication, compared to manual alphabet. About 17.5% of the participants used a cochlear implant or a hearing aid. Most of the individuals lived with a spouse (70%), 20% lived with their parents, 7.5% lived independently, and 2.5% lived with a guardian. The majority of the participants who were married had a child (57.5%). The average Ferrans and Powers' Quality of Life Index (QLI) was 19.33, and the average value for total daily activities was 11.700 MET. The average value for the level of physical activity in males was M = 13716.5 and in females M = 10613.56 (p > 0.05).ConclusionsOverall, we showed that daily activities have a positive effect on the QoL of working individuals with hearing and speech disabilities, i.e., the individuals who had a higher level of physical activity also had a higher QoL.